2010
DOI: 10.1016/j.gtc.2010.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The Safety of Drugs Used in Acid-related Disorders and Functional Gastrointestinal Disorders

Abstract: Acid-related disorders and functional gastrointestinal disorders (FGIDs) are associated with morbidity and impairment of quality of life. However, with the exception of complicated peptic ulcer disease, these disorders do not have appreciable mortality. Treatments for these disorders have consequently been held to a high standard of safety and tolerability by regulatory authorities. Some agents for FGIDs have been withdrawn or restricted based on assessments and perceptions of unfavorable risk/benefit profiles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…Nlrp3 N475K/1 mice were administered 2 to 5 times the maximal doses that had been given intravenously in human studies that had reported a complete lack of adverse effects. [40][41][42] As in other mouse models, 23,43 these doses resulted in no side effects in Nlrp3 N475K/1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…Nlrp3 N475K/1 mice were administered 2 to 5 times the maximal doses that had been given intravenously in human studies that had reported a complete lack of adverse effects. [40][41][42] As in other mouse models, 23,43 these doses resulted in no side effects in Nlrp3 N475K/1 mice.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was significant reduction in the clopidogrel responders subgroup (median 25%, IQR 3–45% vs 53%, IQR 38–65%, p=0.04) with no significant difference in percent inhibition of the rate of platelet aggregation. Although the study concluded that the combination use of PPI and clopidogrel in children with cardiac disease may result in attenuation of clopidogrel's antiplatelet effect, the study's small sample size, observational design, lack of outcomes data, suboptimal PPI dosing, and potential confounding variable with decreased rate of clopidogrel metabolism (e.g., hydrolysis) in infants ideally warrant the need for a study involving a larger sample size in children with cardiovascular disease to ascertain the drug interaction's clinical significance . However, given the propensity of adult data describing this drug interaction and the recommendations from the FDA and Health Canada, this is likely unnecessary.…”
Section: Management Issuesmentioning
confidence: 99%
“… 42 Our experience with the H 2 -receptor antagonists and the PPIs confirm that these are related to the degree and duration of acid suppression rather than drug or dose and include some undesirable effects (e.g., occurrence of fundic polyps, infectious consequences, need to taper the dose when ending long-term treatment etc.). 42 , 43 , 44 , 45 Specific PPI related adverse events are unlikely, due to the different drug (PPI and P-CAB) class and molecular structure of vonoprazan. As adverse events related to the antisecretory effect are still likely to be present and exaggerated, the indications for treatment with this drug should be in keeping with difficult to treat acid-related disorders identified as unmet needs.…”
mentioning
confidence: 99%